Healthy Eating Habits - Martins, L.; Bruno, G. (Open Schools Journal for Open Science, 2020)
This project focuses on the theme of healthy eating habits and is being developed by students from class 8.ºD and under the scope of our school’s social inclusion program. Two questionnaires were applied, one on food and the other on hydration in a school environment, to all classes in the 7th grade and class 8.ºD. In order to alert the school community to the need for good hydration, the class 8.ºD organized a tasting session on flavoured water. In collaboration with the project, the nurse from the school health centre gave two lectures on healthy eating habits. Schools’ shutdown due to Covid-19 pandemic did not allow more sessions to be held, nor to share with the community the questionnaires’ results. Nevertheless, one of the projects main goals is to implement in the school flavoured water dispensers, to encourage students to drink more water.